Improving Vocational Skills on Peanuts Plant of Light Mental Retardation Children at Class IX SLBN I Padang - Tria Handayani; Yarmis Hasan (STAI Miftahul Ula Nganjuk, 2019)
This research is motivated by problems that researchers found in class IX light mental retardation in SLB Negeri I Padang in June 2019. Learning the skills to grow peanuts in light intellectual retardation children, it seems that the work process of children is still not good and right. The objectives of this study are 1. To find out the process of improving peanut planting skills through a demonstration-based method of task analysis in light IX retard children in SLBN 1 Padang. 2. Prove that lightly mental retardation children are skilled at growing groundnuts through demonstration-based methods of task analysis. This type of research is a classroom action research conducted in the form of collaboration between researchers and classroom teachers. As research subjects, two children with light mental retardation grade IX C. Data obtained through observation, and tests of deeds. Then analyzed qualitatively translated through test results. The results of the study after being treated for 7 (seven) meetings showed that the initial ability before the treatment of planting peanuts by BY 28%, and ML 39%. While at the end of the first cycle, BY's ability increased (63%), and ML (68%). In cycle II the ability of BY increased to (89%) and ML (93%). Each cycle begins with planning, implementation, observation, analysis, and reflection. It can be concluded that the implementation of learning by using a method of analysis based on task analysis can improve peanut planting skills in children with intellectual retardation in class IX in SLB Negeri I Padang.